2003
DOI: 10.1017/s1366728903001068
|View full text |Cite
|
Sign up to set email alerts
|

Competing activation in bilingual language processing: Within- and between-language competition

Abstract: Two eye-tracking experiments examined spoken language processing in Russian-English bilinguals. The proportion of looks to objects whose names were phonologically similar to the name of a target object in either the same language (within-language competition), the other language (between-language competition), or both languages at the same time (simultaneous competition) was compared to the proportion of looks in a control condition in which no objects overlapped phonologically with the target. Results support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
382
4
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 481 publications
(457 citation statements)
references
References 45 publications
28
382
4
3
Order By: Relevance
“…This ensured that the participants remained in an English language mode throughout the experiment. Importantly, sound perception and word recognition studies have shown that when L2 learners (especially very advanced ones) are tested entirely in their L2, they have much less interference from their L1 than when they are tested in both languages (Escudero & Boersma, 2002;Kroll & Sunderman, 2003;Marian & Spivey, 2003). Therefore, we believe that the subjects treated the words they learned as English novel words and that they therefore would employ a similar learning mechanism to the present word-learning task as they usually employ in any L2 word-learning situation.…”
Section: Methodsmentioning
confidence: 99%
“…This ensured that the participants remained in an English language mode throughout the experiment. Importantly, sound perception and word recognition studies have shown that when L2 learners (especially very advanced ones) are tested entirely in their L2, they have much less interference from their L1 than when they are tested in both languages (Escudero & Boersma, 2002;Kroll & Sunderman, 2003;Marian & Spivey, 2003). Therefore, we believe that the subjects treated the words they learned as English novel words and that they therefore would employ a similar learning mechanism to the present word-learning task as they usually employ in any L2 word-learning situation.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, support for an asymmetry in native/nonnative phonological processing has come from eye-tracking experiments. While numerous studies found native language activation during non-native language processing (Blumenfeld and Marian 2005;Marian and Spivey 2003a,b;Weber and Cutler 2004;Weber and Paris 2004; but see Spivey and Marian 1999), findings of non-native language activation during native language processing have been mixed (Ju and Luce 2004;Marian and Spivey 2003b;Weber and Cutler 2004). The exact mechanism of the asymmetry in native and non-native language processing remains unknown; however, language proficiency may be an important mediator.…”
Section: Introductionmentioning
confidence: 99%
“…Although only one language (i.e., the target language) is overtly engaged during communication, the bilingual's nontarget language is also coactivated and available, meaning that at any given time, one language is being suppressed (9)(10)(11). The need to constantly control two languages confers advantages in the executive system (12,13), the system that directs cognitive processing.…”
mentioning
confidence: 99%